EFFECTS OF DIGITAL TRANSFORMATION, WORK FORM HOME, ANDEMPLOYEE ENGAGEMENT ON EMPLOYEE PERFORMANCE THROUGH SELF-EFFICIENCY IN THE COVID-19 PANDEMI PERIOD AT THE LURAH OFFICE OF TANJUNGPINANG TIMUR DISTRICT - Balqis, Balqis; Ngaliman, Ngaliman; Satriawan, Bambang (RADJA PUBLIKA, 2022)
The workforce in government agencies is required to adjust to the sudden digital transformation. This appeal from Indonesian President Joko Widodo at a press conference at the Bogor Palace, West Java (15 March 2020) aims to minimize the spread of the Covid-19 Virus which requires people to study from home, worship from home, and carry out any activities at home. Minister of education Nadiem Makariem also appealed to all workers and teachers related to the temporary suspension of learning activities at schools and at universities affected by the Covid-19 virus to carry out teaching and learning from home through application technology. This policy is contained in the circular of the Minister of PAN-RB No.